Authentic Leadership as a Factor in the Development of Positive Psychological Capital (Journal of Universal Excellence, 2026)
Research Question (RQ): How does authentic leadership influence employees and the development of positive psychological capital within organizations?Purpose: This study aimed to conduct a systematic review of both national and international academic literature concerning authentic leadership as a contributing factor to the development of positive psychological capital.Method: We employed a qualitative research approach and a descriptive method, conducting a systematic review of domestic and international scholarly literature from 1998 to 2024. The sources were obtained from publicly accessible databases, including ResearchGate, ScienceDirect, Semantic Scholar, ProQuest, and COBISS, as well as university repositories such as ReVIS, NaRDuS, RUP, RUL, and DKUM. The study examined the significance of the authentic leadership style as a factor in fostering positive interpersonal relationships among employees and in developing positive psychological capital, which contributes to a healthy and constructive organizational ecosystem.Results: The findings of the research provide new theoretical insights that are valuable for informing changes in leadership styles and for future research into various leadership approaches and the key factors associated with organizational success. A leadership style that fosters employee satisfaction has a positive impact on organizational culture.Organization: This study introduces authentic leadership as a managerial model to theorists, researchers, and practitioners engaged in the study of leadership styles, outlining its benefits and challenges, and underscoring its significant potential to facilitate the development of positive social capital within organizational settings."Society: Leadership styles represent patterns of influencing others with the aim of achieving shared goals, whereby the leader employs various levers and tools to shape a leadership approach that is both distinctive and effective. Effective leadership contributes to employee satisfaction and enhances interpersonal relationships in the workplace. These elements collectively strengthen organizational culture and support the sustainable development of both the economy and society.Originality: We identified a gap in the existing research concerning the lack of studies that explicitly link the significance of authentic leadership with the development of positive social capital.Limitations/Future Research: We limited our review to 23 studies, with the selection being subjective and restricted to publicly accessible bibliographic sources. Based on the identified research gaps and findings, we have not only contributed to the field of management science but also offered recommendations for future research.
Keywords: authentic leadership; management; organization; social capital; leadership style; leaders